If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 * 6t + 9 + -10t = 0 Multiply 4 * 6 24t + 9 + -10t = 0 Reorder the terms: 9 + 24t + -10t = 0 Combine like terms: 24t + -10t = 14t 9 + 14t = 0 Solving 9 + 14t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 14t = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 14t = 0 + -9 14t = 0 + -9 Combine like terms: 0 + -9 = -9 14t = -9 Divide each side by '14'. t = -0.6428571429 Simplifying t = -0.6428571429
| 48-x=4*x/7 | | 1/3p=-2 | | 5/2x+3=13 | | 4(x+3y)-24=0 | | (R/s)=(t/(s+t)) | | x^2+-3= | | 3(6k-4.5)=-21.5-5.5k | | -8y+9x-4=0 | | 3m+2*5m-7= | | 5(4/5) | | x^2=2x+20 | | 3n^2-n+4=0 | | -8y+7-4.5y=-27.5 | | (5+2x)*x=403 | | 11a^2-4a-13=0 | | -5+5*x+4= | | 1/5(x-1)=12 | | x/8+6=74 | | 18(x+2)/9x+5 | | (37b-5)-9(4b+1)=-3 | | 5x-7=2x^2+3(3) | | 3.5x+6.5+7=-20.5 | | 18(x+2)=9x+5 | | (47+x)/3=11+x | | -6x^4y^3z-12x^5y^3-18x^4y^2z=0 | | -6x-8=3x+10 | | 5y+2(y-4)=5(y+1)-4 | | 5(2-x)+8=3(x-6) | | (5x-7)=(4x+11)(x) | | 48-x=4*a/7 | | cos*2*x+sin*x=0 | | 5/4x-9/x=2 |